Knowledge and Pacification: On the U.S. Conquest and the Writing of Philippine History - Ariate Jr., Joel F. (Kasarinlan: Philippine Journal of Third World Studies, 2020)
Book review of Ileto, Reynaldo Clemeña. 2017. Knowledge and Pacification: On the U.S. Conquest and the Writing of Philippine History . Quezon City: Ateneo de Manila University Press. xii, 362 pp.